Entrepreneurial strategies for sustainable growth: a deep dive into cloud-native technology and its applications - T. A. Alka; Aswathy Sreenivasan; M. Suresh (Future Business Journal)
Abstract The study highlights the impact of cloud-native technology in entrepreneurship for innovative business models, scalability, and cost efficiency by combining the trends including microservices, serverless computing, and technology disruptions. The study attempts to examine the role of cloud-native technology affects the entrepreneurial landscape in creating and advancing innovative business models and approaches, and the difficulties while applying cloud-native technology. The systematic literature review based on PRISMA is used to explore cloud-native technology and its applications by analyzing selected 111 studies from Scopus, Web of Science, Dimensions, and ProQuest. The study identified that one of the main forces behind disruption is the quick development of new technologies including blockchain, 5G, IoT, quantum computing, and AI. Cloud-native technology supports innovative business models in entrepreneurship such as SaaS, serverless computing, managed Kubernetes, data analytics platforms, BaaS, and Edge Computing. The urgency to incorporate and develop new security features and tools for measurement is necessary. The study shows that startups can use cloud-native technologies for innovative business models that rely on serverless computing, subscription services, and on-demand cloud services which are providing opportunities. The findings of the study highlight the need for entrepreneurs to utilize emerging technologies to meet competition, and there is a requirement for continuous investment in data analytics, automation, cloud solutions, and emerging technologies. Collaboration is essential for the application of the technologies for early stage startups and enterprises. Incubators, accelerators, and venture capital firms support essential to the adoption of disruptive technologies. The policymaker's and enterprises' focus and actionable intervention are necessary for developing mechanisms to solve the barriers of regulatory compliance, lack of skilled manpower, data security, privacy issues, and upfront investment for entrepreneurial success.